Implementation of Islamic Education Management through the Educational Field Introduction Program (PLP) - Izzah Luthvia Rahmah; Lusiani Lusiani; Noval Supriyandi; Amaliyah Amaliyah (CV Edujavare Publishing, 2026)
The Program of Educational Field Introduction (PLP) is an integral component in developing managerial competencies of students in the Islamic Education Management Study Program at Universitas Pamulang by integrating theory and practice of Islamic educational management. This study aims to analyze the implementation of Islamic education management through PLP activities at SDI Darul Ma’arif, focusing on school culture, organizational structure and governance, school regulations, and supporting educational programs. This research employed a qualitative descriptive approach using participatory observation, informal interviews, and documentation studies during the PLP implementation. The findings indicate that SDI Darul Ma’arif demonstrates a strong religious school culture through the habituation of 3S/5S, routine religious activities, and consistent enforcement of school regulations in shaping students’ Qur’anic character. This study concludes that PLP serves as a strategic contextual learning medium in strengthening managerial competencies of Islamic Education Management students and enhancing their understanding of Islamic school management practices